MicroRNA-205-5p regulates the chemotherapeutic resistance of hepatocellular carcinoma cells by targeting PTEN/JNK/ANXA3 pathway - Shao, Ping; Qu, Wei-Kun; Wang, Cheng-Ye; Tian, Yu; Ye, Ming-Liang; Sun, De-Guang; Sui, Ji-Dong; Wang, Li-Ming; Fan, Rong; Gao, Zhen-Ming (American journal of translational research, 2017)
Hepatocellular carcinoma (HCC) is a common malignant tumor of the digestive system, and patients with advanced HCC have a poor outlook, partly due to resistance to chemotherapeutic drugs. Previous studies have implicated microRNAs in the regulation of chemoresistance, and we have previously shown that microRNA (miR)-205-5p is down-regulated in multiple hepatoma cell lines. Here, we investigate whether miR-205-5p is involved in chemotherapeutic resistance in HCC. Expression of miR-205-5p was measured by real-time quantitative reverse transcription PCR and cell viability was determined using a CCK-8 cell viability assay. Expression of proteins in the PTEN/JNK/ANXA3 pathway were assessed via Western blotting. We found that miR-205-5p expression was down-regulated in all HCC cell lines investigated. In addition, miR-205-5p expression was upregulated by 5-fluorouracil (5-Fu) treatment in Bel-7402 (Bel) cells. Interestingly, miR-205-5p expression was increased in multidrug-resistant Bel-7402/5-Fu (Bel/Fu) cells, compared with Bel cells. We next demonstrated that sensitivity to 5-Fu was increased in Bel/Fu cells after treatment with a miR-205-5p inhibitor. Similarly, increased resistance to 5-Fu was observed in Bel cells after transfection with a miR-205-5p mimic. We injected nude mice with Bel/5-Fu cells to promote tumor growth, and found that co-treatment with a miR-205-5p antagomir and 5-Fu slowed tumor growth more than either treatment alone. Finally, we found that these effects were all associated with changes in the PTEN/JNK/ANXA3 pathway. In conclusion, inhibition of miR-205-5p may reverse chemotherapeutic resistance to 5-Fu, and this may occur via the PTEN/JNK/ANXA3 pathway.